2017
DOI: 10.1002/ams2.291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with the difficulty in finding receiving hospitals for traffic accident patients at the scene treated by emergency medical services: a population‐based study in Osaka City, Japan

Abstract: AimAlthough the prolongation of the time between injury and hospital arrival of traffic accident patients can influence their prognosis, factors associated with the difficulty in hospital acceptance of these patients have not been sufficiently evaluated in Japan.MethodsWe retrospectively analyzed the population‐based ambulance records of all traffic accident patients for whom the Osaka Municipal Fire Department (Osaka City, Japan) dispatched an ambulance in 2013. We defined “cases with difficulty in hospital a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…In the Senshu medical control area in Osaka, Japan, Nakao and colleagues reported descriptive results of all emergency patients for whom fire departments had selected medical institutions, but they pointed out that there were excessive limitations to registering them when using a handwritten‐based registry . In contrast, multicenter registry research has been undertaken with the use of information technology, and the establishment of databases that linked ambulance records with in‐hospital information has been also achieved in some areas . Importantly, however, most of these databases were hospital‐based, and there were few population‐based registries at the regional or national level.…”
Section: Introductionmentioning
confidence: 99%
“…In the Senshu medical control area in Osaka, Japan, Nakao and colleagues reported descriptive results of all emergency patients for whom fire departments had selected medical institutions, but they pointed out that there were excessive limitations to registering them when using a handwritten‐based registry . In contrast, multicenter registry research has been undertaken with the use of information technology, and the establishment of databases that linked ambulance records with in‐hospital information has been also achieved in some areas . Importantly, however, most of these databases were hospital‐based, and there were few population‐based registries at the regional or national level.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, when emergency patients call for emergency medical service (EMS) at the scene, on-scene EMS personnel assess the patient’s condition and then transport the patient to a hospital that can accept and treat him or her [ 1 ]. In this process, ambulances can transport the patient to the hospital only after obtaining permission from the selected hospital via a phone call [ 1 ]; this permission is defined as hospital acceptance in Japan [ 2 ]. Recently, the number of emergency patients transported to a hospital by EMS has been increasing and exceeding the hospital capacity in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…We used multivariate logistic regression to find patient characteristics associated with long transportation time. As covariates, distance of transportation from the scene (km), age, sex, reason of transportation (medical or surgical), relevant specialty determined by EMS, condition severity, time of request, weekday or holiday/Sunday, number of EMS negotiations until acceptance, reason for diversion by other hospitals were controlled for, based on a priori knowledge 9,11) .…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated that holiday/weekends or night-times were associated with difficulty in hospital acceptance 10) . A separate study of patients with traumatic injuries demonstrated that pediatric patients, moderate to severe trauma, holiday/weekends or night-times were also associated with difficulty in hospital acceptance 11) . Our study corroborates these prior studies and extends them by demonstrating that patient characteristics among patients transported to NAED were similar to the characteristics of those who experience difficulty in hospital acceptance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation